EVALUATION OF EFFECT OF SHAKTIVARDHAK YOG IN UPPER RESPIRATORY TRACT (URT) INFECTIONS (International Journal of Ayurveda and Pharma Research, 2015)
Upper respiratory tract (URT) infection is one of the common causes of physicians visit for children and associated with significant morbidity. Children with recurrent respiratory tract infections represent a great challenge for the paediatrician, from both therapeutic and preventive standpoints. Still in the modern and Ayurvedic world of treatment there is no permanent cure for common cold exist, but the symptom can be treated accordingly. Thus proposed study aims to study effect of immune booster Shaktivardhak yog to reduce frequency of occurrence of URT infections in order to improve general health condition. Present study includes 30 clinically diagnosed children of URT infection of both the gender having age group 3-5 years. Children were selected randomly and treated with immune booster. Shaktivardhak yog as immune booster yog was given for 12 weeks and follow up taken monthly. It is observed that number of incidences of occurring URT infections decreases significantly as p